Kegiatan Sima'an Al-Qur'an Sebagai Sarana Meningkatkan Hafalan Santri TaḥfῙẓ Putri Di Pondok Pesantren Al-Qur'aniyy Mangkuyudan Surakarta Tahun 2015/2016 - Fajriyah, Holisotul; , Dra. Mahasri Shobahiya, M.Ag (2016)
Al-Quran is the Muslim holy book sent down by Allah. to the Prophet Muhammad. as one apostolic miracle. It is maintained its purity by Allah. By reading and memorizing the holy Qur'an, a Muslim has already maintained the integrity of the Islamic religion. In keeping of memorizing the holy Qur'an, it needs some methods. One of them is by conducting sima'an. Pondok Pesantren Al-Qur'aniyy is an Islamic Boarding House which has engaged in Taḥfīẓ Al-Quran and implemented the sima'an. In implementing the sima'an, there are some supporting and barriering factors. By this case, there are two problem statements that will be discussed in the research: 1) How is the implementation of sima'an can improve Qur'an memorization of women students in Pondok Pesantren Al-Qur'aniyy?. 2) What are the supporting and barriering factors in implementing the sima'an in Pondok Pesantren Al-Qur'aniyy to increase the memorization of the Qur'an?. This research aims to describe the sima'an as a medium to increase the Qur'an memorization of women students in Pondok Pesantren Al-Qur'aniyy Mangkuyudan. It also describes the factors that support and barrier the sima'an activities. This research is a field one with a qualitative descriptive approach. The data are gathered from observation, interviews and documentation, then the data are analyzed with descriptive qualitative analysis, while making conclusion is by using inductive method. The results of this study show that the implementation of sima'an activities in Pondok Pesantren Al-Qur'aniyy Mangkuyudan greatly help students to improve the Qur'an memorization, because the students accustomed to reading and repeating verses will and have already memorized. It is done by demonstrating new memorization and old memorization to their Islamic teacher every day. It is read as much as 0,25 juz with same Taḥfīẓ every Wednesday and Thursday night. The other schedules are peer sima'an Tuesday evening listened by the women students, and sima'an listened by the Islamic teacher and all students on Sunday